The Relationship between Emotional Job Demands and Psychological Well-Being in Nursing Staff at Hospital X: Perceived Organizational Support as Moderator - Neemauli, Elvina Veronica; Radikun, Tulus Budi Sulistyo (GoAcademica Research & Publishing, 2024)
Nurses are required to provide quality care and services to patients in a positive manner regardless of the conditions they experience, thus potentially affecting the psychological well-being of nurses. This study aims to determine the relationship between emotional job demands and psychological well-being with perceived organizational support as a moderator. The participants in this study are 102 nursing staff at Hospital X. The measuring instruments used were the Copenhagen Psychosocial Questionnaire (COPSOQ) which has been translated into Indonesian by Darydzaky & Radikun (2021), the Psychological Well-being Scale (PWBS) which has been translated into Indonesian by Alyani (2021), and the Survey of Perceived Organizational Support (SPOS) which has been translated into Indonesian by Limanda (2017). The results obtained showed that there is a relationship between emotional job demands and psychological well-being (r (173) = -0.31, p < 0.05), while perceived organizational support has no moderating effect on the relationship between emotional job demands and psychological well-being of nursing staff at Hospital X.